Tailoring Ba3PCl3-based perovskite solar cells via multi-parameter optimization for high power conversion efficiency - Bhattarai, Sagar; Banthia, Roshni; Kumar, Abhinav; Alali, Ahmet Sait; Dwivedi, D. K.; Tanti, Bhaben; Maiti, Madhusudan; Dasmahapatra, Suddhendu (NATURE PORTFOLIO, 2026)
Recent research has put the spotlight on PSCs (perovskite solar cells) where leads are not present, because they're better for the environment and have impressive photovoltaic features. Though, the lead-based options like MAPbI(3) are high performers, but their toxicity is a big drawback. In this study, we're introducing Ba3PCl3 as a new, non-toxic absorber material to tackle those environmental worries while keeping strong optoelectronic properties. To boost efficiency, we checked out different electron transport layers (ETLs), and it turns out cerium oxide (CeO2) performed best for improving carrier extraction and reducing recombination. We modelled and optimized the device architecture using SCAPS-1D, focusing on things like absorber thickness and defect density. A comprehensive parametric sweep showed that fine-tuning these factors really makes a difference in device performance. The top configuration achieved a J(SC) (short circuit current density) equal to 43.35 mA/cm(2), a V-OC (open circuit voltage) equal to 0.7059 V, a FF (fill factor) equal to 82.92%, and a PCE (power conversion efficiency) equal to 25.38%.
Keywords: Perovskite solar cells (PSCs); Ba3PCl3; Cerium oxide (CeO2); SCAPS-1D; Power conversion efficiency (PCE); TRANSPORT LAYERS; STABILITY; CEO2; CONDUCTIVITY; ISSUES; Science & Technology - Other Topics